The Central Public Information Repository as a mode of information re-use - Sybilski, Dominik (The Opole Studies in Administration and Law, 2019)
The Central Public Information Repository (CRIP) was introduced into the legal system by the act of 16 September 2011 amending the act on access to public information. The main goal behind the introduction of CRIP was to support the economic exploitation of information. CRIP’s functions are implemented by the Ministry of Administration and Digitization launching an open public data portal (danepubliczne.gov.pl) in May 2014. So far, CRIP has appeared in the literature in the context of access to public information. However, there is a lack of works on CRIP as a national open data portal to distribute information for re-use. This issue in particular has become increasingly important in view of the adoption by the Council of Ministers of the Public Data Access Program, a government strategy dedicated to public policy in the area of open data. Furthermore, due to the entry into force of the Act of 25 February 2016 on the re-use of public sector information, there is an interesting issue about the scope of the CRIP. The article analyzes CRIP regulations in terms of their effectiveness for the implementation of the right to reuse and the policy of open data. The article concludes the findings of the analysis and attempts to propose de lege ferenda conclusion.